Myocardial flow reserve assessed by cardiac 82Rb positron emission tomography/computed tomography is associated with albumin excretion in patients with Type 1 diabetes. (7th December 2018) - Zobel, Emilie H; Winther, Signe A; Hasbak, Philip; von Scholten, Bernt J; Holmvang, Lene; Kjaer, Andreas; Rossing, Peter; Hansen, Tine W
Abstract: Aims: To evaluate myocardial flow reserve (MFR) and coronary artery calcium (CAC) in persons with Type 1 diabetes with or without albuminuria and in non-diabetic controls. MFR reflects the function of large epicardial arteries and myocardial microcirculation. CAC represents structural aspects of atherosclerosis. In addition, we evaluated the association of MFR and CAC with retinopathy, another microvascular complication. Methods and results: Cross-sectional study in Type 1 diabetes, stratified by normoalbuminuria (NORMO; n  = 30) and macroalbuminuria (MACRO; n  = 30), and in non-diabetic controls ( n  = 30). MFR (pharmacological stress flow/rest flow) was evaluated by cardiac 82 Rb positron emission tomography/computed tomography. MFR was similar in patients with NORMO and controls (3.1 ± 0.79 vs. 3.0 ± 0.79; P  =   0.74). Patients with MACRO had lower (impaired) MFR when compared with NORMO (2.1 ± 0.92 vs. 3.1 ± 0.79; P  <   0.0001). The CAC score [median (interquartile range)] was higher in NORMO when compared with controls [72 (22–247) vs. 0 (0–81), P  =   0.03], and comparable between MACRO and NORMO. MFR was comparable in patients with diabetes and simplex or no retinopathy ( n  = 24 and n  = 12, 2.8 ± 0.84 vs. 3.3 ± 0.77, P  =   0.11), but lower in proliferative ( n  = 24) compared with simplex retinopathy (2.1 ± 0.97 vs. 2.8 ± 0.84, P  =   0.02). The CAC score was comparable between groups of retinopathy. Conclusion: Myocardial microvascular function was comparable in non-diabetic controls and patients with Type 1 diabetes and NORMO; but impaired in the presence of microvascular complications (MACRO and proliferative retinopathy). Coronary calcification was elevated in diabetes, however, not explained by albuminuria.